2022
DOI: 10.1155/2022/3959617
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Industrialization on Plant Species Composition, Diversity, and Tree Population Structure in Tropical Moist Deciduous Forest in Bangladesh

Abstract: Industrial activities have various effects on biodiversity, posing significant threats to forest ecosystems. The current study describes the species composition, taxonomic diversity, and stand structure at Bhawal Sal forest, Gazipur, Bangladesh, as they are affected by industrialization. To achieve the goal, 30 different categorized industries within the forest were considered sampling points and three distance gradient sites viz. Site-1 = Adjacent to industries (0 m), Site-2 = 160 m distance and Site-3 = 320 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Measured species richness and β diversity values are comparable with the data collected from phytosociological studies of the same forest area by Kumar et al, (2013). Moreover, β diversity and Simpson's index measures of the present study are also analogous with values obtained from various sites of tropical dry deciduous forests across India by Sagar et al, (2003) ;Nagendra, (2001); Roshni et al, (2022) and Lal et al, (2021).…”
Section: Discussionsupporting
confidence: 87%
“…Measured species richness and β diversity values are comparable with the data collected from phytosociological studies of the same forest area by Kumar et al, (2013). Moreover, β diversity and Simpson's index measures of the present study are also analogous with values obtained from various sites of tropical dry deciduous forests across India by Sagar et al, (2003) ;Nagendra, (2001); Roshni et al, (2022) and Lal et al, (2021).…”
Section: Discussionsupporting
confidence: 87%
“…According to Roshni et al (2023), the three sites' tree stand characteristics-height (m), DBH (cm), density (trees/ha), and basal area-strongly correlated with the biomass carbon stocks of the various tree species. Baul et al (2021) reported that the total soil C stock was strongly correlated with tree structural composition, diversity, and soil properties.…”
Section: Discussionmentioning
confidence: 99%